Comparative analysis of xml functional dependencies - Kamsuriah Ahmad; Hamidah Ibrahim (Penerbit UKM, 2010)
The concept of functional dependency plays a fundamental role in relational databases where they are used to specify constraints and to detect redundancies. Similarly, these constraints will play fundamental role in XML as well. Recently XML functional dependencies (XFDs) have been intensively studied than other constraints for XML data. Since there is no standard definition of XFD for XML, many attempts were made to define XFD. However these definitions capture different types of constraints. Therefore, the objective of this paper is to compare the existing definitions of XFD and propose a new definition of XFD which unifies and generalizes the previous ones. We show that the proposed definition can express more constraints and hence can be used to detect more XML data redundancies than those in previous works.